Color matching in facial prosthetics: A systematic review - Rani Ranabhatt; Kamleshwar Singh; Ramashanker Siddharth; Shuchi Tripathi; Deeksha Arya (Wolters Kluwer Medknow Publications, 2017)
Color matching to the surrounding skin is extremely important in patients wearing maxillofacial prostheses. It is of utmost importance to know the different techniques of color matching and coloring in maxillofacial prostheses. The purpose of this study is to review the literature data with regard to color matching in maxillofacial prosthetics. An electronic search of peer review restricted to English language dental literature was conducted to identify the relevant scientific article on color matching and coloring in maxillofacial prostheses. The publication year was up to December 2015 so that the search could include all the articles provided in that particular database. Two independent observers independently read the abstracts and later preselected full-text articles. A full-text review was carried out only for 15 articles. Out of the 15 articles, 7 were related to coloring using tinting, spraying, milling, and use of commercial cosmetics. Three studies were related to shade matching in maxillofacial prostheses. Two studies conducted the measurement of color in maxillofacial prostheses. Only one study had explained color and its relevance in maxillofacial prosthetics. Only one study was done for reproducing silicone shade guide matching Indian skin color. In addition, a single pilot study was done to measure facial skin and lip color in a human population sample stratified by race, gender, and age. Currently, there is no evidence discussing the best technique available for perfectly matching the color for the fabrication of maxillofacial prostheses. However, the latest instruments such as spectrophotometer and colorimeters are believed to have improved efficiency in matching the color.